Limb lifferences in unipedal balance performance in young male soccer players with different ages - Muehlbauer, T.; Schwiertz, G.; Brueckner, D.; Kiss, R.; Panzer, S. (Sports, 2019)
In soccer, the dominant leg is frequently used for passing and kicking while standing on the non-dominant leg. Consequently, postural control in the standing leg might be superior compared to the kicking leg and is further enhanced with increasing age (i.e., level of playing experience). Unfortunately, leg differences in postural control are associated with an increased risk of injuries. Thus, we examined differences between limbs in unipedal balance performance in young soccer players at different ages. Performance in the Lower Quarter Y Balance Test (YBT-LQ) of the dominant and non-dominant leg and anthropometry was assessed in 76 young male soccer players (under-13 years [U13]: n = 19, U15: n = 14, U17: n = 21, U19: n = 22). Maximal reach distances (% leg length) and the composite scores were used for further analyses. Statistical analyses yielded no statistically significant main effects of leg or significant Leg × Age interactions, irrespective of the measure investigated. However, limb differences in the anterior reach direction were above the proposed cut-off value of >4 cm, which is indicative of increased injury risk. Further, statistically significant main effects of age were found for all investigated parameters, indicating larger reach distances in older (U19) compared to younger (U13) players (except for U15 players). Although reach differences between legs were non-significant, the value in the anterior reach direction was higher than the cut-off value of >4 cm in all age groups. This is indicative of an increased injury risk, and thus injury prevention programs should be part of the training of young soccer players.